A Convenient Conversion of Substituted Cyclohexenones into Aryl Methyl Ketones - Gehring, André P.; Bracher, Franz (Synthesis, 2012)
This work describes a straightforward multistep conversion of substrates containing a cyclohexenone moiety into mono-, bi- and tricyclic aryl methyl ketones in one single working process. Crucial steps are the addition of 1-ethoxyvinyllithium to the carbonyl group, followed by acid-catalyzed enol ether hydrolysis, dehydration, and dehydrogenation.
Keywords: ketones; acetyl anion equivalents; vinyl ether; carbazole; aromatization